Acceleration response spectrum for predicting floor vibration due to occupants jumping. (1st April 2016) - Chen, Jun; Li, Guo; Racic, Vitomir
Highlights: A design-oriented acceleration response spectrum for calculating a floor's response due to jumping crowd. Large number of jumping load records was used in deriving the response spectrum. Comparison of the predicted and field measured response of real floor. Abstract: This paper proposes an acceleration response spectrum to predict floors' responses due to occupants jumping. Experiments were conducted on individual jumping loads resulting in 506 records. Each record was applied to a single-degree-of-freedom system with various frequencies and damping ratios to obtain a corresponding acceleration response spectrum. Statistical analysis of the results led to a representative spectrum, which is further used to derive an analytical design spectrum curve. The suggested design spectrum covers a structural frequency range of 0.5–15 Hz and consists of three main parts: the first plateau, the second plateau and the descent. Design values for spectrum parameters were determined by fitting each part's mathematical function to actual data. The proposed spectrum was verified by comparing its predictions with measured responses from an experimental floor model and floors of existing structures induced by both single individuals and crowds jumping.